Gray-Box Model Identification and Payload Estimation for Delta Robots. Issue 2 (2020) - Falezza, Fabio; Vesentini, Federico; Di Flumeri, Alessandro; Leopardi, Luca; Fiori, Gianni; Mistrorigo, Gianfrancesco; Muradore, Riccardo
Abstract: Delta Robots belong to a class of parallel robots widely used in industrial production processes, mostly for pick-and-place operations. The most relevant characteristics are the high speed and the extremely favorable ratio between the maximum payload and the weight of the robot itself. A reliable dynamic model is needed to implement torque controllers that reduce unnecessary high accelerations and so mechanical vibrations. Moreover, when the mass of the pickable object is unknown, it is crucial to identify with sufficient precision the dynamic contribution of the payload and to accordingly adapt the dynamic model in order to guarantee high performance.